Bibliometric Data Analysis of Research on Resin-Based Brake-Pads from 2012 to 2021 using VOSviewer Mapping Analysis Computations - Nandiyanto, Asep Bayu Dani; Al Husaeni, Dwi Fitria; Ragadhita, Risti (ASEAN Journal for Science and Engineering in Materials, 2023)
This study examines the mapping of research bibliometric data analysis related to resin-based brake pads. The research data was collected through the publish or perish reference manager application from the Google Scholar database. The title of the study material and abstract is used as a basis for searching for availability based on the specified keywords, namely "Resin-based Brake Pads". The search results show a total of 398 articles that are relevant and used in the mapping analysis. VOSviewer is used to complete the mapping process. The study period used as the study material was articles published in Google Scholar indexed journals from 2012 to 2021. We examined the number of published articles on resin-based brake pads and their relationship to problem areas using VOSviewer. The results showed that research on resin-based breake pads experienced an increase in research interest from 2017 to 2021. The smallest number of publications occurred in 2015 with 23 publications. There are main terms that are usually discussed and related to the research theme of resin-based brake pads, namely pad material, development and epoxy resin. This review is expected to serve as a starting point for conducting research by taking the field of study of resin-based brake pads.